Organizational innovation climate and nurses’ innovation behavior in a specialized oncology hospital: the chain mediation of achievement motivation and creative self-efficacy - Xue Fu; Le Xia; Liping Chen; Mei Zhong; Yang Liu; Wenhao He; Baojia Luo; Linmin Chen; Yuying Fan; Huiying Qin (BMC Nursing)
Abstract Objective This study explains the impact of organizational innovation climate on nurses’ innovation behavior in a tertiary specialized oncology hospital, while examining the chain mediation roles of achievement motivation and creative self-efficacy. Methods In this online cross-sectional survey, 857 nurses from a tertiary specialized oncology hospital in Guangdong province, China were selected by convenience sampling method. SPSS Statistics v26.0 and AMOS v29.0 were used for data analysis. The reporting followed the STROBE checklist. Results The nurses’ innovation behavior was below the medium level. Organizational innovation climate was significantly positively related to nurses’ innovation behavior, achievement motivation, and creative self-efficacy. Achievement motivation was positively correlated with both creative self-efficacy and nurses’ innovation behavior. Creative self-efficacy was positively correlated with nurses’ innovation behavior. Mediation analysis identified two pathways: creative self-efficacy independently mediated the relationship between organizational innovation climate and nurses’ innovation behavior, while achievement motivation and creative self-efficacy served as a chain mediator between the organizational innovation climate and nurses’ innovation behavior. Conclusion Our study highlights the critical role of organizational innovation climate in enhancing nurses’ innovation behavior in specialized oncology hospitals. Specifically, it demonstrates that achievement motivation and creative self-efficacy play a chain mediation role between organizational innovation climate and nurses’ innovation behavior. Healthcare administrators should prioritize constructing innovation-supportive climates, implement achievement motivation interventions, and strengthen creative self-efficacy development programs to systematically foster nurses’ innovation capabilities in oncology settings.